2011
DOI: 10.1585/pfr.6.1201009
|View full text |Cite
|
Sign up to set email alerts
|

Ion Acceleration Independent of the Electric Current Direction in Z-Pinch Plasma

Abstract: Ions accelerated in z-pinch experiments with either positive or negative discharge were measured by using a Thomson Parabola analyzer in order to understand the directional tendencies of the ion acceleration. Ions having energy on the order of MeV were observed in both positive and negative discharges. The velocity and energy of each ion species were measured to be considerably similar in magnitude, in spite of the difference in the polarity of the power supplies. The highest-velocity ions with different charg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…These results indicate that ions can be accelerated to have similar energy in both positive and negative discharges. This qualitative tendency in positive and negative discharges is consistent with the previous data shown using Thomson parabola analyzer [13]. The maximum energy of ions in the study is larger than those in the previous study.…”
Section: Ion Transmittance Measurements With Al Foils For Ion Ensupporting
confidence: 92%
See 1 more Smart Citation
“…These results indicate that ions can be accelerated to have similar energy in both positive and negative discharges. This qualitative tendency in positive and negative discharges is consistent with the previous data shown using Thomson parabola analyzer [13]. The maximum energy of ions in the study is larger than those in the previous study.…”
Section: Ion Transmittance Measurements With Al Foils For Ion Ensupporting
confidence: 92%
“…A characteristic ion acceleration has been observed in the divergent gas-puff z-pinch experiment [13]. The results indicated that the acceleration direction of the ions was not affected by the discharge current direction.…”
Section: Introductionmentioning
confidence: 86%
“…High-energy ions up to 1 MeV have been observed in the divergent gas-puff z-pinch experiment. As the ion acceleration has also been observed in the experiment of current reversal, the acceleration has been attributed to some mechanism independent of the current direction 1 . The result indicates that the acceleration mechanism is not the electromagnetic induction, and the understanding of the mechanism is desired.…”
mentioning
confidence: 63%
“…In both of the positive and negative discharges, the xray was generated only from the anode surface, so it was considered that the electrons were accelerated by the induced electromagnetic force at the pinch time. Although ion acceleration independent of current direction has been observed in the divergent gas-puff z-pinch experiment [2], the acceleration mechanism may be different between the ions and electrons.…”
Section: Discussionmentioning
confidence: 99%
“…These ions have been believed to be accelerated by the induced electromagnetic force at the pinch time. On the other hand, ion acceleration independent of the current direction has been observed in the divergent gas-puff z pinch [2].…”
Section: Introductionmentioning
confidence: 99%